Managing in developing countries - Punnett, Betty Jane (Routledge, 2018)
This book considers management theories and approaches specifically in the context of developing countries. In recent years, international business scholarship has increased its focus on the developing world, which represents 80 percent of the global population and has doubled its share of value-added trade in the past two decades. This text will help readers to manage successfully in this region by learning to assess, apply, and adapt established practices in developing countries.